2015
DOI: 10.1021/acs.iecr.5b01187
|View full text |Cite
|
Sign up to set email alerts
|

Optimum Performance of Extractive Desulfurization of Liquid Fuels Using Phosphonium and Pyrrolidinium-Based Ionic Liquids

Abstract: Extractive desulfurization (EDS) of thiophene (T), benzothiophene (BT) and dibenzothiophene (DBT) in simulated fuel using two phosphonium and two pyrrolidinium ionic liquids was investigated. A set of single-factor-at-a-time experiments was carried out to determine factors that significantly affect the EDS process. The single-factor-at-a-time experiments indicate that high sulfur removal (SR) can be achieved using long extraction time (>60 min), high temperature, low fuel-tosolvent ratio (1:4), or large number… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
26
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(27 citation statements)
references
References 23 publications
1
26
0
Order By: Relevance
“…Therefore, as the temperature increased to 30 °C, the miscibility increases as the viscosity decreases, and in turn, S-removal increases while beyond 30 °C S-removal decreased, because of the reverse mitigation. 60,62 The results unveil the inverse effect of temperature on the concentration of DBT in the ILs phase.…”
Section: Instrumentationmentioning
confidence: 84%
“…Therefore, as the temperature increased to 30 °C, the miscibility increases as the viscosity decreases, and in turn, S-removal increases while beyond 30 °C S-removal decreased, because of the reverse mitigation. 60,62 The results unveil the inverse effect of temperature on the concentration of DBT in the ILs phase.…”
Section: Instrumentationmentioning
confidence: 84%
“…Literature reviews show that increasing the size of cation/anion of ionic liquid increases the ionic liquid's ability for sulfur removal [1,[3][4][5][6]. Also, the larger alkyl chain of cation/anion and cation symmetry cause more capacity of ionic liquid to sulfur removal [8][9][10][11][12][13][14][15][16][17][18]. It should be noted that an experimental testing approach is very time-consuming, and detecting of appropriate ionic liquid is even unrealistic.…”
Section: Introductionmentioning
confidence: 99%
“…Most extractive desulfurization studies conduct experimentally for selecting ionic liquids. The structural features of ionic liquid such as cation family, cation alkyl chain length, anion nature, etc., play an important role in removing sulfur compounds from fuels [1,[3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18]. Literature reviews show that increasing the size of cation/anion of ionic liquid increases the ionic liquid's ability for sulfur removal [1,[3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…The utilization of ILs in liquid–liquid extraction and in extractive distillation , is a promising technology to separate close boiling point mixtures. The relative simple synthesis and low viscosity of pyrrolidinium-based IL are found to add a practical value in various applications, and this also includes possible extraction of sulfur compounds from fuels and observed to reveal high selectivities in (aliphatic/aromatic) extraction processes. Activity coefficient data for solutes which are soluble in water are very important because water is a universal solvent utilized in various industrial productions for making new chemical compounds. Activity coefficients can be predicted by several methods, but only a limited number of studies reported activity coefficients at infinite dilution for compounds in water, γ 13 ∞ , and very few of them are performed over a range of temperatures. …”
Section: Introductionmentioning
confidence: 99%